LOSSES TO SAMOGITIAN JEWS’ DOCUMENTARY HERITAGE DURING WORLD WAR I - Petreikis, Tomas (Knygotyra, 2017)
In 1914, the Samogitian Jews were exposed to the first adverse consequences of World War I. Thus, the town centre of Žemaičių Naumiestis was burnt down; more than 50 local Jewish libraries were destroyed from fire. In 1915, deportations of the Jewish population into the depths of Russia began. More intense activities by the German troops on the borderline resulted in huge material and human losses. The period in question was marked by cases of thefts and wilful destruction of Jewish documentary heritage. However, in most cases Jews’ belongings and assets perished in the fire together with their houses that had been set fire to. More significant losses incurred as a result of military actions were experienced in the spring of 1915 by the Jews living in Paprūsė (Podlesi region), Šiauliai country and the Courland border. During the research, 92 cases of losing the Jewish documentary heritage were established. Relevant data were collected on the essential aspects of preserving and losing documentary heritage in the period of 1914–1918. More in-depth analysis was conducted on the losses of Jewish documentary heritage in Gruzdžiai, Jurbarkas, Kelmė, Kuršėnai, Raseiniai, Leckava, Seredžius, Švėkšna, Tirkšliai, Tauragė ir Žemaičių Naumiestis. The total value of these losses amounts to 96 thousand roubles. Among the most valuable were the manuscript libraries collected by Torah and Jewish communities as well as archival collections. The Jews were known to have established a great number of libraries; even the illiterate Jews had personal collections of books. Quite a few Jewish libraries stored a 1000 and more volumes of books. Due to the significant losses of both archival documents and human demography, the author could not further develop the reconstruction of this heritage on a larger scale. However, the material collected made it possible to identify and evaluate the common problems of preserving and losing Samogitian Jews’ documentary heritage during World War I.